La administración de la bula de la Santa Cruzada en Nueva España (1547-1659) - Martínez López-Cano, María del Pilar (El Colegio de México, A.C., 2013)
The Bull of the Crusade was one of the most original sources of income for the Real Hacienda. It consisted of charity provided by the faithful in exchange for indulgences, exemptions from fasting, and other spiritual privileges; this church rent was handed over to the Catholic monarchy after negotiations between the Crown and the Holy See. The predication of the bull in the viceroyalty began officially in 1574; this work examines how this revenue was levied from that year until 1659, a period characterized by the system of asientos generales (general entries), thus called because the contract included all the bishoprics in New Spain, Guatemala, and the Philippines. The author provides data on treasurers, collections, and entry conditions, and reflects on the opportunities opened by these arrangements.